ANALISIS PROSES PEMBELAJARAN PERKALIAN MELALUI METODE BERNYANYI DENGAN 10 JARI DI MI THORIQOTUL HIDAYAH - Zuschaiya, Diana; Salsabila, Eka Aprilia; Kartika, Amalia Dwi; Rohmah, Linda Auliya’ur; Aristin, Asmitha Auliya (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
The use of inappropriate learning methods can hinder the achievement of learning objectives, including mastery of multiplication concepts in Mathematics. One alternative method that can be implemented to teach multiplication is the singing method. This study aims to analyze the implementation of the singing method using ten fingers in teaching multiplication at MI Thoriqotul Hidayah, Karangwungulor, Lamongan. This research employs a descriptive qualitative method with a case study approach. Data were collected through direct observation, interviews, and documentation. The findings reveal that the implementation of the singing method using ten fingers is based on the concept of repeated addition in multiplication learning. The advantages of this method include enhancing students’ concentration and facilitating understanding of basic multiplication concepts. However, its drawbacks are the relatively long time required for implementation and the use of loud voices, which may disrupt learning activities in other classes. The challenges encountered include limited instructional time and students’ varying levels of ability. This becomes a particular obstacle, especially for students with lower cognitive abilities, who tend to struggle with the method and thus fail to achieve learning mastery. Therefore, further research is needed to explore more effective solutions to address these challenges in the learning process.